Candida krusei, a Multidrug-Resistant Opportunistic Fungal Pathogen: Geographic and Temporal Trends from the ARTEMIS DISK Antifungal Surveillance Program, 2001 to 2005 - (:unkn) unknown (My University, 2008)
ABSTRACT Candida krusei is well known as a fungal pathogen for patients with hematologic malignancies and for transplant recipients. Using the ARTEMIS Antifungal Surveillance Program database, we describe geographic and temporal trends in the isolation of C. krusei from clinical specimens and the in vitro susceptibilities of 3,448 isolates to voriconazole as determined by CLSI (formerly NCCLS) disk diffusion testing. In addition, we report the in vitro susceptibilities of bloodstream infection isolates of C. krusei to amphotericin B (304 isolates), flucytosine (254 isolates), anidulafungin (121 isolates), caspofungin (300 isolates), and micafungin (102 isolates) as determined by CLSI broth microdilution methods. Geographic differences in isolation were apparent; the highest frequency of isolation was seen for the Czech Republic (7.6%) and the lowest for Indonesia, South Korea, and Thailand (0 to 0.3%). Overall, 83% of isolates were susceptible to voriconazole, ranging from 74.8% in Latin America to 92.3% in North America. C. krusei was most commonly isolated from hematology-oncology services, where only 76.7% of isolates were susceptible to voriconazole. There was no evidence of increasing resistance of C. krusei to voriconazole from 2001 to 2005. Decreased susceptibilities to amphotericin B (MIC at which 90% of isolates were inhibited [MIC 90 ], 4 μg/ml) and flucytosine (MIC 90 , 16 μg/ml) were noted, whereas 100% of isolates were inhibited by ≤2 μg/ml of anidulafungin (MIC 90 , 0.06 μg/ml), micafungin (MIC 90 , 0.12 μg/ml) or caspofungin (MIC 90 , 0.25 μg/ml). C. krusei is an uncommon but multidrug-resistant fungal pathogen. Among the systemically active antifungal agents, the echinocandins appear to be the most active against this important pathogen.
Candida krusei , a Multidrug-Resistant Opportunistic Fungal Pathogen